1991
DOI: 10.1111/j.1460-9568.1991.tb00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Regulation of Cytosolic Ca2+ Concentration by Adenosine and α1‐Adrenergic Agonists in Mouse Striatal Astrocytes

Abstract: Adenosine has a broad array of actions on neurons but astrocytes also possess adenosine receptors. We have previously shown that adenosine, by acting on astrocytes in the striatum, can modulate neuronal responses mediated by receptors coupled to phospholipase C through an astrocyto - neuronal interaction. In addition, adenosine was found to potentiate the alpha1-adrenergic production of inositol phosphates in astrocytes. The mechanism involved in this potentiation was further investigated by examining the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…This study extends the use of the technique from previous applications in, for example pituitary cells (Mollard et al, 1989), cultured rat spinal neurones (Schieren & MacDermot, 1988) and astrocytes (Delumeau et al, 1991 by Simpson et al (1993), who have demonstrated that the rise in intracellular free calcium levels evoked by NMDA receptor activation is essentially due to calcium entry. Moreover, Frandsen et al (1989) demonstrated that glutamic acid directly stimulated 45Ca2" entry into cultured cortical neurones.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This study extends the use of the technique from previous applications in, for example pituitary cells (Mollard et al, 1989), cultured rat spinal neurones (Schieren & MacDermot, 1988) and astrocytes (Delumeau et al, 1991 by Simpson et al (1993), who have demonstrated that the rise in intracellular free calcium levels evoked by NMDA receptor activation is essentially due to calcium entry. Moreover, Frandsen et al (1989) demonstrated that glutamic acid directly stimulated 45Ca2" entry into cultured cortical neurones.…”
Section: Discussionmentioning
confidence: 50%
“…This is in agreement with our previous work on the release of D-[3H]-aspartate from cerebellar granule cells, where, again, the inhibitory effect of riluzole was abolished by pertussis toxin . These data suggest that the interaction between riluzole and excitatory amino acid-mediated events may involve activation of a pertussis toxin-sensitive G-protein, perhaps by directly activating a coupled receptor (such an interaction has been observed between adenosine and o-adrenoceptors on astrocytes by Delumeau et al (1991)). …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Incubation media were recovered and centrifuged for 5 min at 200 ϫ g to eliminate nonadherent cells, and the radioactivity was estimated in the supernatant. HPLC analysis, performed as described previously (Delumeau et al, 1991), indicated that Ͼ95% of the radioactivity is recovered in a peak having the same retention time as authentic AA.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence indicating that the relative importance of the Na + /Ca 2+ exchanger in different types of glial cells is highly variable [5][6][7][8][9][10][11][12][13]. Furthermore, its role has sometimes not been conclusively proved.…”
mentioning
confidence: 99%